Long noncoding RNA ADIRF antisense RNA 1 upregulates insulin receptor substrate 1 to decrease the aggressiveness of osteosarcoma by sponging microRNA-761. Issue 2 (1st February 2022) - Xu, Lingling; Tan, Yinling; Xu, Fengxia; Zhang, Yong
ABSTRACT: An increasing number of studies have supported the critical regulatory actions of long noncoding RNAs (lncRNAs) in osteosarcoma (OS). However, the detailed roles of adipogenesis regulatory factor-antisense RNA 1 (ADIRF-AS1) in OS have not been comprehensively described. Hence, we first detected ADIRF-AS1 expression in OS and evaluated its clinical significance. Functional experiments were then performed to determine the modulatory role of ADIRF-AS1 in OS progression. ADIRF-AS1 was found to be overexpressed in OS, and the overall survival of patients with OS who had high ADIRF-AS1 levels was shorter than that of those with low levels. ADIRF-AS1 knockdown led to restricted proliferation, migration, and invasiveness of OS cells and increased apoptosis. Additionally, ADIRF-AS1 downregulation impeded tumor growth in vivo . Mechanistically, ADIRF-AS1 acted as a competitive endogenous RNA for microRNA-761 (miR-761) that siphoned miR-761 away from its target, namely insulin receptor substrate 1 (IRS1), leading to IRS1 overexpression. Rescue experiments showed that low levels of miR-761 or restoration of IRS1 could neutralize the effects of ADIRF-AS1 ablation in OS cells. In summary, ADIRF-AS1 exacerbates the oncogenicity of the OS cells by targeting the miR-761/IRS1 axis. Our findings may aid in the advancement of lncRNA-directed therapeutics for OS.